PENDIDIKAN LITERASI PADA ANAK DALAM PERSPEKTIF AL QUR’AN - M. Romadlon Habibulloh; Achmad Anwar Abidin (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
The discussion in this article focuses on Literacy Education in children in the perspective of Al qur’an with the method of combining a comprehensive search of academic databases, scientific articles, books, and other relevant sources to collect information about Literacy Education in children in the perspective of the Qur'an. Of course, these sources are confirmed books of exegesis. The essence of literacy from the perspective of the Qur'an is QS. Al-Alaq verses 1-5 is where one can use one's intellect to think, one's heart to feel, and one's senses to help one find meaning. contains commandments and obligations for everyone to learn and teach them. Which learning in this verse is symbolized by two terms namely iqra 'and qalam with the meaning of reading and writing as widely as possible. As well as the form of God's teaching to his servants, which is symbolized by teaching either through the medium of a pen (qalam) or God's direct teaching ('allama) as exemplified by Allah that He Himself will teach man. The things that must be done in literacy education to early childhood are: reading stories to children regularly, storytelling by telling stories, doing letter recognition, writing practice, making visits to the library and limiting screen time.